Optimal combination of anti-inflammatory components from Chinese medicinal formula Liang-Ge-San. (6th April 2021) - Lu, Zibin; Cao, Huihui; Liu, Dongyi; Zheng, Yuanru; Tian, Chunyang; Liu, Shanhong; Quan, Jingyu; Shi, Lingzhu; Liu, Junshan; Yu, Linzhong
Abstract: Ethnopharmacological relevance: Liang-Ge-San (LGS), a traditional Chinese medicine (TCM) formula, is usually used in acute inflammatory diseases in China. Aim of the study: This study aims to detect the optimal combination of anti-inflammatory components from LGS. Materials and methods: Four mainly representative components (phillyrin, emodin, baicalin, and liquiritin) from LGS were chosen. The optimal combination was investigated by orthogonal design study. Zebrafish inflammation model was established by lipopolysaccharide (LPS)-yolk microinjection, and then the anti-inflammatory activities of different combinations were determined by survival analysis, changes on inflammatory cells infiltration, the MyD88/NF-κB and MAPK pathways and inflammatory cytokines production. Results: The different combinations of bioactive ingredients from LGS significantly protected zebrafish from LPS-induced inflammation, as evidenced by decreased recruitment of macrophages and neutrophils, inhibition of the MyD88/NF-κB and MAPK pathways and down-regulation of TNF-α and IL-6. Among them, the combination group 8 most significantly protected against LPS. The combination of group 8 is: 0.1 μM of emodin, 2 μM of baicalin, 20 μM of phillyrin and 12.5 μM of liquiritin. Conclusion: The optimized combination group 8 exerts the most significant anti-inflammatory activity by inhibiting the recruitment of inflammatory cells, activation of the MyD88/NF-κB and MAPK pathways and the secretion of pro-inflammatory cytokines. This present study provides pharmacological evidences for the further development of new modern Chinese drug from LGS to treat acute inflammatory diseases, but indicated the use of zebrafish in the screening of components from formulas. Graphical abstract: Image 1